Microscopia eletrônica de varredura: aspectos instrumentais - Santos, Maria Júlia dos (Universidade Federal de São Carlos, 2024)
Scanning electron microscopy (SEM) arose from the need to characterize materials on the nanometer scale, considering that until then, optical microscopes could only achieve resolutions of the order of micrometers. Since the beginning of the 20th century, many studies have been carried out by different scientists to arrive at the model of scanning electron microscope used today. It was from their discoveries, such as the fact that this type of microscope allows analyzing different types of samples, that SEM became one of the main characterization techniques in the field of science. Therefore, given the relevance of this equipment, it is extremely important that researchers have knowledge about its instrumental part. With this in mind, the present work seeks to show how a scanning electron microscope works, explaining each of its main components and giving a general overview of electronic optics, which is directly correlated to the subject. The first component presented was the electron gun, which talked about thermionic emission guns and tunneling emission guns, in addition to the three most common types of filament: tungsten (W), lanthanum hexaboride (LaB6) and field emission gun (FEG). The second component was the lens system, where it was described how the lenses operate and the possible effects of aberrations. Finally, this work describes the third component, which are the detectors, explaining which device is used for each of the two most common signals generated during the scanning process, which are the secondary electron signal and the backscattered electron signal.
Scanning electron microscopy: instrumental aspects
Keywords: Canhão de elétrons; Lentes eletrostáticas; Lentes magnéticas; Microscopia eletrônica de varredura; Óptica eletrônica; Electron gun; Electrostatic lenses; Magnetic lenses; Scanning electron microscopy; Electron optics; CIENCIAS EXATAS E DA TERRA::QUIMICA